Os efeitos da escolha sob estresse dos operadores de pregão no mercado financeiro através da metodologia do Iowa Gambling Task - Santos, Augusto Felippe Caramico dos (2018)
This thesis aims to investigate if traders have better decision management under stress, obtaining greater financial results. The Iowa Gambling Task was used to verify the hypothesis of research and the influence of the somatic markers in decision making, integrated to the theories of Behavioral Finance and Emotional Finance. The results indicated trading floor operators has better quality of decision making, faster learning, greater adaptability and superior financial result compared to control group. Among the subgroups of operators, there was a significant difference in the learning process and financial result obtained, demonstrating better ability to recognize patterns and higher financial results of the floor traders when compared to the group of electronic desk traders